Lincoln in private : what his most personal reflections tell us about our greatest president - White, Ronald C. (Ronald Cedric), 1939-; White, Ronald C. (Ronald Cedric), 1939- (Random House, 2021)
"The first full-color facsimile edition of Lincoln's private notes, Abraham Lincoln's Diary is a deluxe collection of some of his most revelatory private writings. An essential archive, here presented exactly as Lincoln wrote them on scraps of paper, these "notes to self" appear alongside original, contextualizing essays by New York Times bestselling presidential biographer Ronald C. White. A deeply private man, closed off to even those who worked closely with him, Lincoln often captured "his best thoughts" in these notes--never wanting "one of those ideas to escape." In Abraham Lincoln's Diary, White offers this rare glimpse into the thought process of one of our nation's most important orators and presidents. The book selects ten of Lincoln's most revealing notes, reproduced here in full color, allowing us to see this little-known but vital body of Lincoln's writing, in which he grapples with the problem of slavery; attempting to find convincing rebuttals to those who supported the evil institution; or prepares for his historic debates with Stephen Douglas in the midst of his 1858 senatorial campaign. In one fragment, written on the eve of his inauguration, we see Lincoln develop an argument for national unity amidst a secession crisis that would ultimately rend the nation in two. Arranged in chronological order, beginning in 1848 with a note that was written just one year into Lincoln's Congressional term as an Illinois representative, Abraham Lincoln's Diary is a wholly original volume that grants us fresh insight into our nation's greatest president."--